Mandarin Chinese wh-in-situ argument–adjunct asymmetry in island sensitivity: Evidence from a formal judgment study - Tian, Qilin; Park, Myung-Kwan; Yang, Xiaodong (Frontiers in Psychology, 2022)
Unlike adjunct wh’s-in-situ, argument wh’s-in-situ do not seem to be subject to island constraints in Chinese and other East Asian languages. This difference in island sensitivity between argument and adjunct wh’s-in-situ is known as argument–adjunct asymmetry in the theoretical literature. Recently, this long-established asymmetry is challenged by a formal judgement study. It was claimed in the study that this asymmetry is an illusion and both argument and adjunct wh’s-in-situ are subject to island constraints. This paper demonstrates that such a claim is not convincing because it is based on problematic experimental design. We designed two experiments to test the island effects on Chinese wh’s-in-situ. The results reaffirm that the argument–adjunct asymmetry in Chinese wh’s-in-situ is indeed present, contrary to the findings of previous formal judgement study, and they also corroborate our assumption that when object wh’s-in-situ like shénme ‘what’ are located inside a relative clause, they are subject to a pragmatic constraint, suggesting that the VP (formed by a verb and its wh-object) in the relative clause tends to describe the prominent/salient feature of the relativized nominal head.